The influence of tinnitus acceptance on the quality of life and psychological distress in patients with chronic tinnitus - Riedl, David (Noise Health, 2015)
Recent findings show the importance of acceptance in the treatment of chronic tinnitus. So far, very limited research investigating the different levels of tinnitus acceptance has been conducted. The aim of this study was to investigate the quality of life (QoL) and psychological distress in patients with chronic tinnitus who reported different levels of tinnitus acceptance. The sample consisted of outpatients taking part in a tinnitus coping group (n = 97). Correlations between tinnitus acceptance, psychological distress, and QoL were calculated. Receiver operating characteristic (ROC) curves were used to calculate a cutoff score for the German “Tinnitus Acceptance Questionnaire” (CTAQ-G) and to evaluate the screening abilities of the CTAQ-G. Independent sample t-tests were conducted to compare QoL and psychological distress in patients with low tinnitus acceptance and high tinnitus acceptance. A cutoff point for CTAQ-G of 62.5 was defined, differentiating between patients with “low-to-mild tinnitus acceptance” and “moderate-to-high tinnitus acceptance.” Patients with higher levels of tinnitus acceptance reported a significantly higher QoL and lower psychological distress. Tinnitus acceptance plays an important role for patients with chronic tinnitus. Increased levels of acceptance are related to better QoL and less psychological distress.